Diagnostic value of plasma lysophosphatidic acid levels in ovarian cancer patients: A case–control study and updated meta‐analysis. Issue 12 (16th October 2015) - Cao, Liyan; Zhang, Yunjie; Fu, Zhanzhao; Dong, Lixin; Yang, Sen; Meng, Wei; Li, Yiyang; Zhang, Wenchao; Zhang, Jialing; Zheng, Changjun; Zhu, He; Fan, Limei
Abstract: Aim: We investigated whether plasma levels of lysophosphatidic acid (LPA) could serve as a diagnostic indicator for assessing disease progression in ovarian cancer (OC) patients. Material and Methods: In this study, we enrolled 98 patients with OC, 70 patients with benign ovarian tumors and 75 healthy controls. Plasma levels of LPA and cancer antigen 125 (CA‐125) were measured in all study subjects. The diagnostic values of LPA and CA‐125 plasma levels were evaluated and an updated meta‐analysis was performed to examine the association between LPA plasma levels and OC progression. Statistical analyses were performed withspss 18.0 and R 3.1.0 software. Results: In our case–control study, OC patients showed significantly higher plasma LPA levels compared to patients with benign tumors and healthy controls (all P < 0.05). Plasma LPA levels exhibited higher diagnostic sensitivity ( P = 0.008) and specificity ( P = 0.042) in detecting OC, compared to an established marker, CA‐125. Notably, the sensitivity for early stage OC was significantly higher for plasma LPA levels in comparison to CA‐125 ( P < 0.05). Consistent with this, the area under the receiver–operator curve was greater for LPA (0.899) in comparison to that for CA‐125 (0.751). Further, meta‐analysis showed that plasma LPA levels were significantly higher in OC patients compared to patients with benign tumors or healthy controls (all P < 0.05). Conclusion: Plasma LPA levels are elevated in OC patients and correlate with disease progression. Further, LPA shows higher sensitivity and specificity in OC diagnosis, compared to CA‐125, especially in early stage OC.